Perancangan Media Pembelajaran Berbasis Augmented Reality Pengenalan Akomodasi Perhotelan di SMK Global Pariaman - Ulandari, Intan Tri; Efriyanti, Liza (Institut Teknologi Pendidikan Indonesia, 2023)
This research was conducted from the existence of problems found after observations were made at SMK Global Pariaman which found the problem that students and teachers only rely on manual learning and still use printed books, worksheets without using computer technology-based learning media. up-to-date and 3 D (three dimensions). Therefore, the authors are interested in designing learning media based on Augmented Reality in order to increase students' interest in learning, while the aim of this research is to produce a valid, practical and effective Augmented Reality-based learning support media design for Hospitality Accommodation. The method used in this study is the Research and Development (R&D) method using the Luther-Sutopo version of theMultimedia Development Life Cycle (MDLC), which consists of six stages, namely concept, design. design), material collecting (collection of material), assembly (manufacturing), testing (testing) and distribution (distribution). And there are three product tests carried out in this study, namelyvalidity tests given to expert lecturers or subject matter experts, practicality tests conducted bystudy teachers in the Hospitality Accommodation subject and effectiveness tests given to studentsin SMK Global Pariaman X. According to the results of product tests that have been carried out by the author from the validity test, the average value is 0.8 which is declared valid, and for the practicality test, the average value is 0.88. which is stated to be practical and for the effectiveness test to get the average value is 0.76 which is declared effective.